Estudio de prefactibilidad para la instalación de una planta productora de filtrantes a base de muña (Minthostachys mollis) y culén (Psoralea glandulosa L.) - Agüero Molina, Alonso Enrique (2022)
Currently, a naturalistic trend has been generated in the world, which consists in the increase in the consumption of herbal products, such is the case of fillets based on muña and culen that, thanks to their curative and digestive properties, help to combat gastritis. This trend allowed to find a market in which the project can be developed. To determine the specific demand of the present study, the historical data of a substitute product (green tea) was analyzed to find the apparent internal demand. Projected this trend with a linear regression (2021 to 2025) and segmenting it under the urban population over 16 years of socioeconomic levels A, B and C of Metropolitan Lima and data collected from the survey as intensity, intention and preference factor. The ranking of factors for macro localization and micro localization was used in order to find the most suitable place for the implementation of the production plant. For plant size, technology size was considered as limiting with a capacity of 23 748 kg / year. The bottleneck is drying with a capacity of 20 kg / hour. Likewise, the layout of the plant in which an area of 896 m² was determined was made. The investment of the project is S/ 406 907. When determining the income from sales, costs and expenses that the project will have, the economic VAN S/ 311 064, economic TIR 50,58%, financial VAN S/ 493 803 and financial TIR 91,55% and when compared with the COK 22,81%, it can be concluded that the project is viable.